2019
DOI: 10.1038/s41467-019-09274-y
|View full text |Cite
|
Sign up to set email alerts
|

High-quality mesoporous graphene particles as high-energy and fast-charging anodes for lithium-ion batteries

Abstract: The application of graphene for electrochemical energy storage has received tremendous attention; however, challenges remain in synthesis and other aspects. Here we report the synthesis of high-quality, nitrogen-doped, mesoporous graphene particles through chemical vapor deposition with magnesium-oxide particles as the catalyst and template. Such particles possess excellent structural and electrochemical stability, electronic and ionic conductivity, enabling their use as high-performance anodes with high rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(91 citation statements)
references
References 63 publications
(51 reference statements)
1
90
0
Order By: Relevance
“…An obvious cathodic peak at around 0.5 V appeared in the first cycle and then disappeared in the following cycles, which indicated that a solid electrolyte interphase (SEI) layer from the electrolyte decomposition was formed in the first cycle. The CV profiles are generally consistent with the reported graphene electrode from the second cycle . From second to fifth cycles, the CV curves are almost overlapped, indicating the stable reversible Li + storage reactions of HGF.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…An obvious cathodic peak at around 0.5 V appeared in the first cycle and then disappeared in the following cycles, which indicated that a solid electrolyte interphase (SEI) layer from the electrolyte decomposition was formed in the first cycle. The CV profiles are generally consistent with the reported graphene electrode from the second cycle . From second to fifth cycles, the CV curves are almost overlapped, indicating the stable reversible Li + storage reactions of HGF.…”
Section: Resultssupporting
confidence: 85%
“…We next compared the LIBs performance of HGF with representative anode in other studies (such as graphene and Si) and state‐of‐the‐art commercial graphite anodes. As far as we know, such a high area capacity HGF electrode with high mass loading even after a large number of cycles has rarely been reported for graphene and Si electrode materials with high theoretical capacity (Figure a), and the area capacity of HGF electrode is higher than the commercial graphite electrode materials although the HGF electrodes were tested at higher current density . In contrast, we further compare the areal capacity versus current density of HGF with researched graphene, graphite and Si anodes, and commercial graphite anodes .…”
Section: Resultsmentioning
confidence: 89%
“…In recent years, a huge boost has been observed in areas such as nanotechnology and nanoscience, being important the advances obtained in biomedicine [ 122 ], energy [ 123 ], catalysis [ 124 ] and electronic [ 125 ]. To a large extent, it has been due to the development and incorporation of new nanomaterials.…”
Section: Ecl Enzymatic Biosensorsmentioning
confidence: 99%
“…Recently, graphene has been widely used in electrochemical sensing, photoelectric conversion and electromechanical sensing [15][16][17][18] owing to its superior electroconductivity, high thermal conductivity and great mechanical strength. [19][20][21][22] Compared to graphene, graphene oxide (GO), which is the derivative of graphene, has fascinating properties for a functional design.…”
Section: Introductionmentioning
confidence: 99%